Considerations for Mandibular Reconstruction in the Pediatric Patient Following Resection of Malignant Tumors. Issue 2 (March 2019) - Nam, Jung Woo; Nam, Woong; Cha, In Ho; Kim, Hyung Jun
Abstract : Abstract: We recently achieved favorable results in 3 pediatric patients with mandibular osteosarcomas that were treated at our hospital, including with immediate reconstructive surgery performed after tumor resection. Based on a literature review and practical investigation, we discuss the considerations for mandibular reconstruction after malignant lesions are removed from the mandible in children. Mandibular reconstruction for pediatric patients requires an understanding of the changes in bone and soft-tissue architecture due to growth and development at both the donor and recipient sites. Immediate mandibular reconstruction with a free flap can be considered a reasonable option even for young children who require extensive mandibular surgery. However, the variables affecting decisions about treatment planning vary between the different conditions in individual patients, and moreover, these cases are not common in the pediatric population. Therefore, long-term follow-up treatment and further investigations are required for the optimized diagnosis, treatment, and prognosis of pediatric mandibular malignancies.